2015
DOI: 10.1038/nri3859
|View full text |Cite|
|
Sign up to set email alerts
|

Eicosanoid storm in infection and inflammation

Abstract: Controlled immune responses to infection and injury involve complex molecular signaling networks with coordinated and often opposing actions. Eicosanoids and related bioactive lipid mediators derived from polyunsaturated fatty acids constitute a major bioactive lipid network, which is among the most complex and challenging pathways to map in a physiological context. Eicosanoid signaling, similar to cytokine signaling and inflammasome formation, has been viewed as primarily a pro-inflammatory component of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
1,124
2
33

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,192 publications
(1,174 citation statements)
references
References 119 publications
15
1,124
2
33
Order By: Relevance
“…Prostaglandins, leukotrienes and lipoxins are groups of eicosanoids involved in pro-, and/or anti-inflammatory responses. During vasodilation prostaglandins and leukotrienes induce increased permeability of post capillary venules and also recruit complement components and leukocytes to the site of inflammation [2]. In contrast, lipoxins act as pro-resolving lipid mediators, as for example, LXA 4 inhibits the recruitment of neutrophil and eosinophil granulocytes in post capillary venules [3].…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins, leukotrienes and lipoxins are groups of eicosanoids involved in pro-, and/or anti-inflammatory responses. During vasodilation prostaglandins and leukotrienes induce increased permeability of post capillary venules and also recruit complement components and leukocytes to the site of inflammation [2]. In contrast, lipoxins act as pro-resolving lipid mediators, as for example, LXA 4 inhibits the recruitment of neutrophil and eosinophil granulocytes in post capillary venules [3].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, RvD1 was found to limit nuclear localization of 5-LO in Mfs via inhibition of calmodulindependent protein kinase II (48). As reviewed by Dennis and Norris (6), the availability of endogenous AA to the different COX and LOX enzymes and assembly of enzyme systems may also apply. Expression of 15-LOX-1 was higher in M-CSF Mfs as compared with GM-CSF cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was reported that LXA 4 and 15-epi-LXA 4 could also be formed within one cell type (murine RAW264.7 and bone marrow-derived Mfs) (8). Depending on the expression and activation of eicosanoid-forming enzymes and their proximity to cPLA 2 , cells may preferentially shunt AA toward one of these pathways (6). Lipidomic analysis has been applied to study AA metabolism in mouse peritoneal Mfs (9), RAW264.7 Mfs (10,11), mouse mast cells (12), and Mfs from mouse lung tumors (13).…”
mentioning
confidence: 99%
“…Of course, we were excited to see that the new questions raised by their discoveries pointed back to our favorite enzyme, PLA 2 . Specifically, free arachidonic acid is at very low levels in cells and is generated spontaneously as needed for prostaglandin/leukotriene biosynthesis; PLA 2 is responsible for the initiation of this arachidonic acid cascade (9,78,81) (Fig. 6).…”
Section: A Turning Point For Lipid Signalingmentioning
confidence: 99%
“…Back in my laboratory, lipid cell signaling had always been focused on the metabolites of arachidonic acid-the eicosanoids and related oxidized polyunsaturated fatty acids (PUFA)-that activate a large variety of G-coupled protein receptors (GPCRs) (81). We had already learned through our work on cobra venom sPLA 2 that inhibitors could help us interrogate enzymes, but the inhibitors that worked on sPLA 2 didn't necessarily translate well to the mammalian systems, especially the intracellular PLA 2 s that now occupied our attention.…”
Section: A Turning Point For Lipid Signalingmentioning
confidence: 99%